NONPROFIT COMMUNICATIONS a mission-driven and human-centered approach. - Gaggin, Kelly ([S.l.] : ROUTLEDGE, 2024)
This text provides a guide to strategic communications for nonprofit organizations that is rooted in the desire to serve and do good. Acknowledging that nonprofit organizations, like commercial businesses, cannot succeed without a communications strategy that supports their overall business goals, seasoned practitioner and educator Kelly C. Gaggin explores the industry in a way that nurtures the servant's heart while clearly discussing the business structure of nonprofits and the need (in most cases) to earn revenue to provide services. She teaches a strategic and integrated approach to communications that is mission-based and human-centric to align the values of the nonprofit sector with the campaign planning process. This text offers a view of nonprofits at local, national, and international levels of impact and explores those relationships while keeping in mind the value and needs of those being served. This book is an indispensable text for undergraduate and graduate courses in nonprofit strategic communications and/or management as well as an essential resource for nonprofit industry professionals. Online resources also accompany this text. For instructors: lecture slides, syllabus, chapter quizzes. For students: planning templates for DEEEM model. Please visit www.routledge.com/9781032461144.
Keywords: Nonprofit organizations; Business communication; BUSINESS & ECONOMICS / Public Relations